Do community demographics, environmental characteristics and access to care affect risks of developing ACOS and mortality in people with asthma?. Issue 3 (11th September 2017) - To, Teresa; Zhu, Jingqin; Carlsten, Christopher; Larsen, Kristian; Ryckman, Kandace; Feldman, Laura Y.; Crighton, Eric; Lougheed, M. Diane; Licskai, Christopher; Villeneuve, Paul J.; Su, Yushan; Sadatsafavi, Mohsen; et al.
Individuals with asthma and chronic obstructive pulmonary disease (COPD) overlap syndrome (ACOS) have a more rapid decline in lung function, more frequent exacerbations and worse quality of life than those with asthma or COPD alone [1–3]. Various risk factors may be associated with the development of ACOS, such as smoking history and status, obesity, comorbidity and indoor and outdoor environmental exposures [1, 4–6]. The risk of developing ACOS may vary substantially by region, since demographic and environmental risk factors and community characteristics are not geographically homogeneous. Here, we use population-based data to estimate the incidence of ACOS in the asthma population and to measure the association between demographic factors, community-level characteristics and environmental factors and the risk of incident ACOS and all-cause mortality while accounting for spatial autocorrelation. Material deprivation increases ACOS and death risk in people with asthma; air pollution may also increase death risk http://ow.ly/Eb8730dRPPc